A highly magnetized twin-jet base pinpoints a supermassive black hole - Baczko, Anne-Kathrin; Schulz, Robert; Kadler, Matthias; Ros, Eduardo; Perucho, Manel; Krichbaum, T. P.; Boeck, M.; Bremer, M.; Großberger, Christoph; Lindqvist, M.; Lobanov, A. P.; Mannheim, K.; et al. (Astronomy & Astrophysics, 2016)
Supermassive black holes (SMBH) are essential for the production of jets in radio-loud active galactic nuclei (AGN). Theoretical models based on (Blandford & Znajek 1977, MNRAS, 179, 433) extract the rotational energy from a Kerr black hole, which could be the case for NGC 1052, to launch these jets. This requires magnetic fields on the order of 10G to 10G. We imaged the vicinity of the SMBH of the AGN NGC 1052 with the Global Millimetre VLBI Array and found a bright and compact central feature that is smaller than 1.9 light days (100 Schwarzschild radii) in radius. Interpreting this as a blend of the unresolved jet bases, we derive the magnetic field at 1 Schwarzschild radius to lie between 200 G and 8.3 × 10 G consistent with Blandford & Znajek models.
Keywords: Galaxies: active; Galaxies: jets; Galaxies: magnetic fields; Galaxies: nuclei; Magnetic fields

ANTARES constrains a blazar origin of two IceCube PeV neutrino events - Adrian-Martinez, S.; Albert, A.; Andre, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Astronomy & Astrophysics, 2015)
Results. Both blazars predicted to be the most neutrino-bright in the TANAMI sample (1653-329 and 1714-336) have a signal flux fitted by the likelihood analysis corresponding to approximately one event. This observation is consistent with the blazar-origin hypothesis of the IceCube event IC 14 for a broad range of blazar spectra, although an atmospheric origin cannot be excluded. No ANTARES events are observed from any of the other four blazars, including the three associated with IceCube event IC20. This excludes at a 90% confidence level the possibility that this event was produced by these blazars unless the neutrino spectrum is flatter than -2.4.
Keywords: neutrinos; galaxies: active; quasars: general

Millimeter VLBI of NGC 1052: Dynamics - Baczko, Anne-Kathrin; Schulz, Robert; Ros, Eduardo; Kadler, Matthias; Perucho, Manel; Wilms, Jörn (Galaxies, 2016)

TANAMI blazars in the IceCube PeV-neutrino fields - Krauß, Felicia; Kadler, Matthias; Mannheim, K.; Schulz, Robert; Truestedt, J.; Wilms, Jörn; Ojha, R.; Ros, Eduardo; Anton, Gisela; Baumgartner, W.; Beuchert, Tobias; Blanchard, J.; et al. (Astronomy & Astrophysics, 2014)
The IceCube Collaboration has announced the discovery of a neutrino flux in excess of the atmospheric background. Owing to the steeply falling atmospheric background spectrum, events at PeV energies most likely have an extraterrestrial origin. We present the multiwavelength properties of the six radio-brightest blazars that are positionally coincident with these events using contemporaneous data of the TANAMI blazar sample, including high-resolution images and spectral energy distributions. Assuming the X-ray to gamma-ray emission originates in the photoproduction of pions by accelerated protons, the integrated predicted neutrino luminosity of these sources is high enough to explain the two detected PeV events.
Keywords: neutrinos; galaxies: active; quasars: general

TANAMI monitoring of Centaurus A: The complex dynamics in the inner parsec of an extragalactic jet - Mueller, C.; Kadler, Matthias; Ojha, R.; Perucho, Manel; Großberger, Christoph; Ros, Eduardo; Wilms, Jörn; Blanchard, J.; Boeck, M.; Carpenter, B.; Dutka, M.; Edwards, P. G.; et al. (Astronomy & Astrophysics, 2014)
Context. Centaurus A (Cen A) is the closest radio-loud active galactic nucleus. Very Long Baseline Interferometry (VLBI) enables us to study the spectral and kinematic behavior of the radio jet-counterjet system on milliarcsecond scales, providing essential information for jet emission and propagation models.Aims. In the framework of the TANAMI monitoring, we investigate the kinematics and complex structure of Cen A on subparsec scales. We have been studying the evolution of the central parsec jet structure of CenA for over 3.5 years. The proper motion analysis of individual jet components allows us to constrain jet formation and propagation and to test the proposed correlation of increased high-energy flux with jet ejection events. Cen A is an exceptional laboratory for such a detailed study because its proximity translates to unrivaled linear resolution, where one milliarcsecond corresponds to 0.018 pc.Methods. As a target of the southern-hemisphere VLBI monitoring program TANAMI, observations of CenA are done approximately every six months at 8.4 GHz with the Australian Long Baseline Array (LBA) and associated telescopes in Antarctica, Chile, New Zealand, and South Africa, complemented by quasi-simultaneous 22.3 GHz observations.Results. The first seven epochs of high-resolution TANAMI VLBI observations at 8.4 GHz of CenA are presented, resolving the jet on (sub-) milliarcsecond scales. They show a differential motion of the subparsec scale jet with significantly higher component speeds farther downstream where the jet becomes optically thin. We determined apparent component speeds within a range of 0 : 1 c to 0 : 3 c and identified long-term stable features. In combination with the jet-to-counterjet ratio, we can constrain the angle to the line of sight to theta similar to 12 degrees-45 degrees.Conclusions. The high-resolution kinematics are best explained by a spine-sheath structure supported by the downstream acceleration occurring where the jet becomes optically thin. On top of the underlying, continuous flow, TANAMI observations clearly resolve individual jet features. The flow appears to be interrupted by an obstacle causing a local decrease in surface brightness and circumfluent jet behavior. We propose a jet-star interaction scenario to explain this appearance. The comparison of jet ejection times to high X-ray flux phases yields a partial overlap of the onset of the X-ray emission and increasing jet activity, but the limited data do not support a robust correlation.
Keywords: galaxies: active; galaxies: individual: Centaurus A; galaxies: individual: NGC 5128; techniques: high angular resolution; galaxies: jets

TANAMI: Tracking Active Galactic Nuclei with Austral Milliarcsecond Interferometry - Mueller, C.; Kadler, M.; Ojha, R.; Schulz, Robert; Truestedt, J.; Edwards, P. G.; Ros, E.; Carpenter, B.; Angioni, R.; Blanchard, J.; Böck, Moritz; Burd, P. R.; et al. (Astronomy & Astrophysics, 2018)
Context. TANAMI is a multiwavelength program monitoring active galactic nuclei (AGN) south of -30 degrees declination including high-resolution very long baseline interferometry (VLBI) imaging, radio, optical/UV, X-ray, and gamma-ray studies. We have previously published first-epoch 8.4 GHz VLBI images of the parsec-scale structure of the initial sample. In this paper, we present images of 39 additional sources. The full sample comprises most of the radio-and gamma-ray brightest AGN in the southern quarter of the sky, overlapping with the region from which high-energy (>100 TeV) neutrino events have been found.Aims. We characterize the parsec-scale radio properties of the jets and compare them with the quasi-simultaneous Fermi/LAT gamma-ray data. Furthermore, we study the jet properties of sources which are in positional coincidence with high-energy neutrino events compared to the full sample. We test the positional agreement of high-energy neutrino events with various AGN samples.Methods. TANAMI VLBI observations at 8.4 GHz are made with southern hemisphere radio telescopes located in Australia, Antarctica, Chile, New Zealand, and South Africa.Results. Our observations yield the first images of many jets below -30 degrees declination at milliarcsecond resolution. We find that gamma-ray loud TANAMI sources tend to be more compact on parsec-scales and have higher core brightness temperatures than gamma-ray faint jets, indicating higher Doppler factors. No significant structural difference is found between sources in positional coincidence with high-energy neutrino events and other TANAMI jets. The 22 gamma-ray brightest AGN in the TANAMI sky show only a weak positional agreement with high-energy neutrinos demonstrating that the >100 TeV IceCube signal is not simply dominated by a small number of the gamma-ray brightest blazars. Instead, a larger number of sources have to contribute to the signal with each individual source having only a small Poisson probability for producing an event in multi-year integrations of current neutrino detectors.
Keywords: galaxies: active; galaxies: jets; galaxies: nuclei; radio continuum: galaxies; techniques: high angular resolution; neutrinos

The TANAMI Multiwavelength Program: Dynamic spectral energy distributions of southern blazars - Krauß, Felicia; Wilms, Jörn; Kadler, Matthias; Ojha, R.; Schulz, Robert; Truestedt, J.; Edwards, P. G.; Stevens, J.; Ros, Eduardo; Baumgartner, W.; Beuchert, Tobias; Blanchard, J.; et al. (Astronomy & Astrophysics, 2016)
Context. Simultaneous broadband spectral and temporal studies of blazars are an important tool for investigating active galactic nuclei (AGN) jet physics. Aims. We study the spectral evolution between quiescent and flaring periods of 22 radio-loud AGN through multiepoch, quasi-simultaneous broadband spectra. For many of these sources these are the first broadband studies. Methods. We use a Bayesian block analysis of Fermi/LAT light curves to determine time ranges of constant flux for constructing quasi-simultaneous spectral energy distributions (SEDs). The shapes of the resulting 81 SEDs are described by two logarithmic parabolas and a blackbody spectrum where needed. Results. The peak frequencies and luminosities agree well with the blazar sequence for low states with higher luminosity implying lower peak frequencies. This is not true for sources in high states. The γ-ray photon index in Fermi/LAT correlates with the synchrotron peak frequency in low and intermediate states. No correlation is present in high states. The black hole mass cannot be determined from the SEDs. Surprisingly, the thermal excess often found in FSRQs at optical/UV wavelengths can be described by blackbody emission and not an accretion disk spectrum. Conclusions. The so-called harder-when-brighter trend, typically seen in X-ray spectra of flaring blazars, is visible in the blazar sequence. Our results for low and intermediate states, as well as the Compton dominance, are in agreement with previous results. Black hole mass estimates using recently published parameters are in agreement with some of the more direct measurements. For two sources, estimates disagree by more than four orders of magnitude, possibly owing to boosting effects. The shapes of the thermal excess seen predominantly in flat spectrum radio quasars are inconsistent with a direct accretion disk origin.
Keywords: BL Lacertae objects: general; Galaxies: active; Quasars: general; Relativistic processes

The unusual multiwavelength properties of the gamma-ray source PMN J1603-4904 - Müller, Cornelia; Kadler, Matthias; Ojha, R.; Boeck, M.; Krauß, Felicia; Taylor, G. B.; Wilms, Jörn; Blanchard, J.; Carpenter, B.; Dauser, Thomas; Dutka, M.; Edwards, P. G.; et al. (Astronomy & Astrophysics, 2014)
Context. We investigate the nature and classification of PMN J1603-4904, a bright radio source close to the Galactic plane, which is associated with one of the brightest hard-spectrum gamma-ray sources detected by Fermi/LAT. It has previously been classified as a low-peaked BL Lac object based on its broadband emission and the absence of optical emission lines. Optical measurements, however, suffer strongly from extinction and the absence of pronounced short-time gamma-ray variability over years of monitoring is unusual for a blazar.Aims. In this paper, we are combining new and archival multiwavelength data of PMN J1603-4904 in order to reconsider the classification and nature of this unusual gamma-ray source.Methods. For the first time, we study the radio morphology of PMN J1603-4904 at 8.4 GHz and 22.3 GHz, and its spectral properties on milliarcsecond scales, based on VLBI observations from the TANAMI program. We combine the resulting images with multiwavelength data in the radio, IR, optical/UV, X-ray, and gamma-ray regimes.Results. PMN J1603-4904 shows a symmetric brightness distribution at 8.4 GHz on milliarcsecond scales, with the brightest, and most compact component in the center of the emission region. The morphology is reminiscent of a compact symmetric object (CSO). Such objects, thought to be young radio galaxies, have been predicted to produce gamma-ray emission but have not been detected as a class by the Fermi gamma-ray telescope so far. Sparse (u, v)-coverage at 22.3 GHz prevents an unambiguous modeling of the source morphology at this higher frequency. Moreover, infrared measurements reveal an excess in the spectral energy distribution (SED), which can be modeled with a blackbody with a temperature of about 1600 K, and which is usually not present in blazar SEDs.Conclusions. The TANAMI VLBI data and the shape of the broadband SED challenge the current blazar classification of one of the brightest gamma-ray sources in the sky. PMN J1603-4904 seems to be either a highly peculiar BL Lac object or a misaligned jet source. In the latter case, the intriguing VLBI structure opens room for a possible classification of PMN J1603-4904 as a gamma-ray bright CSO.
Keywords: galaxies: active; galaxies: individual: PMNJ1603-4904; radio continuum: general; gamma rays: galaxies; techniques: interferometric; X-rays: galaxies